Impact and elastic modulus of coal mining on terrestrial ecosystems - Jihong Dong; Wenting Dai; Jiren Xu; Hui Zhang; Yunpeng Li; Fei Xie (Scientific Reports)
Abstract The energy consumption structure is gradually evolving into a "diversified energy structure" against the backdrop of the global implementation of energy-saving and low-carbon policies. Coal, as the main energy source in China, is difficult to change in the short term, given the characteristics of China’s energy and resource endowments, as well as the actual social and economic development at the present stage. Nevertheless, coal mining inevitably leads to a range of ecological issues. Identifying the impact of coal mining on terrestrial ecosystems and adopting resilient recovery measures are crucial prerequisites for advancing green coal mining efforts and attaining carbon peaking and carbon neutrality goals. Using China’s open-pit coal mining as a case study: (1) the research examines the fundamental attributes and evolving patterns of spatial distribution among these mines within the country. Furthermore, it delineates the life cycle stages and distinctive features of the five principal open-pit coal mines. The life cycle of a coal mining area is divided into four distinct development phases: the initial phase, the accelerated phase, the stable phase, and the declining phase. The spatial relationship between the life cycle stages of coal mining and ecosystem succession is elucidated by examining the evolutionary types of ecosystems within coal mine area. In the accelerated and stable development phase, the adverse effects of coal mining on the ecosystem are in a long-term increasing trend, causing the key elements of the ecosystem to gradually surpass their threshold values. The ecosystem is out of balance, severely damaged, and gradually undergoing degradation or extreme degradation. The types of ecological succession in coal mining areas can be categorized as follows: terrestrial succession leading to a new terrestrial ecosystem, terrestrial to aquatic ecosystem transitions, or the development of an amphibious symbiotic ecosystem. (2) The research quantitatively assessed the impact of surface coal mining on terrestrial ecosystems by utilizing remote sensing data in conjunction with coal production information. In 2022, the affected areas of the five major open-pit coal mines due to coal mining activities amounted to approximately 0.02% of China’s total land area. Meanwhile, the nationwide affected areas of all open-pit coal mines combined reached to approximately 0.13% of China’s land area. Open-pit coal mining activities have a significant impact on the surface. (3) By incorporating the ecological resilience theory, we establish a model for the ecosystem’s elastic modulus in coal mining areas, taking into account landscape diversity, vegetation coverage, land type, and climate factors, which are based on the concepts of elastic strength and elastic limit. A conceptual model for recognizing ecological thresholds in coal mining areas is developed by incorporating the comprehensive integrity index of the ecosystem. The comprehensive integrity of the ecosystem within a coal mining area undergoes significant alterations as it crosses three distinct ecological thresholds: the elastic point, the yield point, and the mutational point. There should be a corresponding constant (or constant interval) at the three ecological thresholds of ecosystem resilience, the elastic point, the yield point, and the mutational point, which is closely related to the scale of mining operations, mining technology, and the service life in coal mining areas. The established models for identifying ecological thresholds and the resilience modulus degree serve as both theoretical references and practical bases for managing the progress and trends of ecosystem changes during coal resource extraction, making ecological restoration in coal mine areas more target-oriented and specific.